HEALTH PROMOTION BEFORE THE HIV/AIDS EPIDEMIC IN PRIMARY CARE IN PUNTA ARENAS - Velásquez, Mónica Rosas; Meirelles, Betina Hörner Schlindwein; Suplici, Samara Eliane Rabelo (My University, 2020)
ABSTRACT Objective: to identify the attitudes and actions of health professionals in health promotion before the HIV/AIDS epidemic in Primary Health Care (PHC), Punta Arenas, Magallanes and Chilean Antartica Chilena region, Chile. Method: a qualitative, descriptive, and exploratory study carried out at PHC facilities in the city of Punta Arenas, Chile. Sixteen professionals who work in the five Family Health Centers participated. Data collection was carried out between March and May 2019. Data was obtained through a semi-structured interview. To organize data, ATLAS ti® was used, which were analyzed according to thematic content analysis. Results: two categories have emerged. The first category, Health promotion and prevention actions before HIV/AIDS, described the actions carried out by nurses in their daily work, such as counseling on STI/AIDS prevention, sexual/reproductive health and education for professionals and the community. The second category, Nurse-midwives' attitudes towards caring for people living with HIV/AIDS, includes caring without prejudice, active behavior and empathy due to high workload. Conclusion: health promotion and prevention actions carried out by PHC professionals are mainly related to counseling and education for professionals and the community. The need to integrate prevention measures with other professionals and vulnerable groups in the community stands out.
Keywords: hiv; acquired immunodeficiency syndrome; health personnel; nursing; primary prevention; health promotion